Visible and NIR Upconverting Er3+–Yb3+ Luminescent Nanorattles and Other Hybrid PMO‐Inorganic Structures for In Vivo Nanothermometry. (9th June 2020) - Kaczmarek, Anna M.; Suta, Markus; Rijckaert, Hannes; Abalymov, Anatolii; Van Driessche, Isabel; Skirtach, Andre G.; Meijerink, Andries; Van Der Voort, Pascal
Abstract: Lanthanide‐doped luminescent nanoparticles are an appealing system for nanothermometry with biomedical applications due to their sensitivity, reliability, and minimal invasive thermal sensing properties. Here, four unique hybrid organic–inorganic materials prepared by combining β‐NaGdF4 and PMOs (periodic mesoporous organosilica) or mSiO2 (mesoporous silica) are proposed. PMO/mSiO2 materials are excellent candidates for biological/biomedical applications as they show high biocompatibility with the human body. On the other hand, the β‐NaGdF4 matrix is an excellent host for doping lanthanide ions, even at very low concentrations with yet very efficient luminescence properties. A new type of Er 3+ –Yb 3+ upconversion luminescence nanothermometers operating both in the visible and near infrared regime is proposed. Both spectral ranges permit promising thermometry performance even in aqueous environment. It is additionally confirmed that these hybrid materials are non‐toxic to cells, which makes them very promising candidates for real biomedical thermometry applications. In several of these materials, the presence of additional voids leaves space for future theranostic or combined thermometry and drug delivery applications in the hybrid nanostructures. Abstract : New hybrid materials developed by combining (β‐NaGdF4 :Er, Yb) with periodic mesoporous organosilicas or mesoporous silica are shown to be excellent luminescent thermometers for physiological temperatures with suitable luminescence both in the visible and the first biological transparency window. The materials are proven to be completely non‐toxic to human fibroblastic cells showing excellent potential as future nanothermometers for biological systems.